Pengelolaan Zakat untuk Pemberdayaan Masyarakat Miskin pada Badan Amil Zakat di Kabupaten Bojonegoro - Nadya Septiana Wulansari; iswadi Siswadi; Arif Maghfur (Al-Muzdahir : Jurnal Ekonomi Syariah, 2021)
Zakat is a pillar of islam the must be issued by every muslim by fulfilling certain condition. Zakat contains two dimensions, namely direct worship to Allah and worship to fellow human beings. Zakat is worship that prioritizes social values in addition to spiritual values. in addition, the empowerment of zakat funds, if managed properly, will improve the economy of the poor at the productif age.This type of research includes field research, which is a research that is carried out systematically by lifting data from the field. By using qualitative research methods that produce deskriptive data in the form of written or spoken words form poeple and observed behavior. The result of this study indicate that the strategy used by BAZNAS of Bojonegoro Regency and ASN, Civil Servants, BUMN, BUMD, as well as various agencies. Institutions and mosques to intruduce the importance of zakat and establish UPZ (Zakat Collection Unit). The programs carried out by the Religious Bojonegoro, Genius Bojonegoro, philanthropic Bojonegoro, Productive Bojonegoro. And for the community empowerment program, namely the Productive Bojonegoro Program, the activities of this program have been going well and can improve the mustahiq economy which is provided by the productive Bojonegoro program. The obstacle experienced by BAZNAS in Bojonegoro regency during zakat management is that there is still a lack of public awareness of the importance of paying zakat and when during the pandemic BAZNAS redusec gathering activities and is more active on social media.